Cognitive-Behavioral Therapy for Obsessive–Compulsive Disorder with and without Autism Spectrum Disorder: Gray Matter Differences Associated with Poor Outcome - Tsuchiyagaito, Aki; Hirano, Yoshiyuki; Asano, Kenichi; Oshima, Fumiyo; Nagaoka, Sawako; Takebayashi, Yoshitake; Matsumoto, Koji; Masuda, Yoshitada; Iyo, Masaomi; Shimizu, Eiji; Nakagawa, Akiko (Frontiers in Psychiatry, 2017)
Cognitive Behavioral Therapy (CBT) is an effective treatment for Obsessive-Compulsive Disorder (OCD) and is also applicable to patients with both OCD and Autism Spectrum Disorder (ASD). However, previous studies have reported that CBT for patients with both OCD and ASD might be less effective than for patients with OCD alone. In addition, there is no evidence as to why autistic traits might be risk factors. Therefore, we investigated whether comorbidity between ASD and OCD may significantly affect treatment outcome, and discovered predictors of CBT outcomes using structural magnetic resonance imaging (MRI) data. A total of 39 patients, who were diagnosed with OCD, were enrolled in this study. Of these, except for 2 dropout cases, 15 patients were diagnosed with ASD, and 22 patients were diagnosed with OCD without ASD. Both groups took CBT for 11 to 20 sessions. First, to examine the effectiveness of CBT for OCD patients with and without ASD, we compared CBT outcomes between the two groups. Second, to investigate how the structural abnormality profile of the brain at pre-treatment influenced CBT outcomes, we performed a structural MRI comparison focusing on the gray matter volume of the whole brain in both patients with only OCD, and those with both OCD and ASD. In order to discover neurostructural predictors of CBT outcomes besides autistic traits, we divided our samples again into two groups of those who did and those who did not remit after CBT, and repeated the analysis taking autistic traits into account. The results showed that OCD patients with ASD responded significantly less well to CBT. The OCD patients with ASD had much less gray matter volume in the left occipital lobe than OCD patients without ASD. The non-remission group had a significantly smaller volume of gray matter in the left dorsolateral prefrontal cortex (DLPFC) compared with the remission group, after having partialled out autistic traits. These results indicate that the abnormalities in DLPFC negatively affect the CBT outcome, regardless of the severity of the autistic traits.